Ruthenium red attenuates brown adipose tissue thermogenesis in rats - Lillo Vizin, Robson Cristiano (2021)
Ruthenium red (RR) is a non-selective antagonist of the temperature-sensitive Transient Receptor Potential (TRP) channels and it is an important pharmacological tool in thermoregulatory research. However, the effect of RR on thermoeffector activity is not well established. Here we evaluated the effect of RR on cold-defense thermoeffectors induced by menthol, an agonist of the cold-sensitive TRPM8 channel. Adult male Wistar rats were used. Epidermal treatment with menthol raised deep body temperature due to an increase in oxygen consumption (an index of thermogenesis), a reduction in heat loss index (an index of cutaneous vasoconstriction), and an induction in warmth-seeking behavior in a two-temperature choice apparatus. Pretreatment with RR attenuated the menthol-induced increase in deep body temperature and oxygen consumption, but it did not affect heat loss index and warmth-seeking behavior. To stimulate brown adipose tissue thermogenesis, rats were treated with CL 316,243, a potent and selective beta 3-adrenoceptor agonist. CL 316,243 increased deep body temperature, which was attenuated by RR pretreatment. We conclude that RR reduces brown adipose tissue thermogenesis induced by menthol and CL 316,243, independent of effects at the thermal sensor level (i.e., TRPM8).